Assessment of plant diversity in homegardens of three ecological zones of Nepal - Pokhrel, Chandra Prasad (Ecoprint: An International Journal of Ecology, 2016)
Homegardens in Nepal have long been regarded as one of the most important multi-propose agroforestry systems with complex structure. The aim of the study was to assess the species diversity and richness in three different ecological regions, i.e., Mountain (Sub-alpine), Mid-hill (Temperate) and Terai (Tropical) of Nepal. In total 45 homegardens were randomly selected and examined from three different villages representing one from each ecological regions and the Shannon–wiener, Simpson index and evenness were assessed. Overall 147 species were identified mainly vegetable, fruit, fodder, spices or medicinal plants. The average size of homegardens were found to be bigger in Mid-hill (0.12 ha), however, the species number and diversity was found to be high in the Terai region (102). More similarity between plant species composition was between Terai and Mid-hill. The Shannonwiener index was found to be 1.316, 1.84 and 1.90 in the homegarden of Mountain, Mid-hill and Terai respectively. Simpson index was 0.052, 0.014 and 0.01 in homegarden of Mountain, Mid hill and Terai region, respectively. Similarly, evenness percentage was 56.29, 65.55 and 65.93 in homegarden of Mountain, Mid-hill and Terai region, respectively. Properly managed homegardens have high productivity and increased sustainability which helps in conserving agro-biodiversity, food sufficiency and economic supports including other ecological functions. ECOPRINT 22: 63-74, 2015